Pertanggungjawaban Notaris Atas Pembuatan Akta Pernyataan Kepemilikan Bersama Pada Sebidang Tanah (Studi Kasus Putusan Nomor 191/Pdt.G/2019/Pn.Sda) - Utami, Vanessa; Yuslim; Fauzi, Wetria (Universitas Ekasakti, 2025)
Notaries as public officials who are authorized to make authentic deeds are regulated in the Notary Law Number 30 of 2004 as amended by Law Number 2 of 2014 concerning the Notary Law (UUJN). Authentic deeds function as valid evidence in civil law according to Article 1870 of the Civil Code (KUHPerdata). However, in exercising their authority, notaries are required to ensure the material validity of the deeds made, especially regarding the object of joint property rights as regulated in Articles 35 and 36 of Law Number 1 of 1974 concerning Marriage and Article 119 of the Civil Code. The formulation of the problem in this study is How is the judge's legal consideration of court decision number 191 / Pdt.G / 2019 / PN.Sda related to the making of a deed of joint ownership statement on a plot of land, how is the notary's responsibility for making a deed of joint ownership statement on a plot of land in court decision number 191 / Pdt.G / 2019 / PN.Sda, The purpose of writing this thesis is To find out and analyze the judge's legal considerations regarding court decision number 191 / Pdt.G / 2019 / PN.Sda related to making a deed of joint ownership statement on a plot of land, To find out and analyze the notary's responsibility for making a deed of joint ownership statement on a plot of land in court decision number 191 / Pdt.G / 2019 / PN.Sda, the method used in this study is normative juridical. The study shows that the judge in this decision considered the deed of joint ownership statement to be null and void because it was made without the consent of both husband and wife which is a basic requirement as regulated in Article 36 of the Marriage Law. The judge stated that the defendants' actions were unlawful acts that were detrimental to the plaintiff, so that the deed did not have binding legal force. In terms of accountability, the notary was declared negligent in ensuring the involvement of all parties interested in the joint property. As a result, the deed made was declared null and void by law, and the notary was responsible civilly, administratively, and the notary's code of ethics in accordance with the provisions of the Notary Law.